Energy demand modeling for the Philippine cement industry sector - Gerra, Lheander G.
This thesis describes a bottom-up model for the Philippines cement manufacturing sector. The model is composed of a baseline year model for 2015, and projections of cement production and energy consumption for reference and alternative scenarios. An econometric model was used to estimate the energy intensity and demand for manufacturing cement product. Using economic indicators such as GDP and cement prices, the projected energy demand for cement production under different scenarios were investigated. Cement production and energy demand were projected for three possible GDP growth rates. Aside from energy demand projection, energy savings potential per plant was also investigated through application of different energy efficiency programs which targets the improvements of energy efficiency of different technologies used in the cement production process. Based on results, biggest energy saving potential would be achieved through using energy efficient kiln technologies during the clinkering stage process and energy efficient mill grinders during the cement grinding process. Lastly, the global warming potential of the whole cement industry as well as possible reduction potential under different scenarios were investigated. Based on results, fuel switching (from coal to biomass fuels) has the marginal GWP reduction potential by the end of 2050.